Severe Pediatric Head Injury During the Iraq and Afghanistan Conflicts. Issue 1 (July 2015) - Klimo, Paul; Ragel, Brian T.; Jones, G. Morgan; McCafferty, Randall
Abstract : BACKGROUND: Much has been written about injuries sustained by US and coalition soldiers during the Global War on Terrorism campaigns. However, injuries to civilians, including children, have been less well documented. OBJECTIVE: To describe the epidemiologic features and outcomes associated with isolated severe head injury in children during Operations Enduring Freedom and Iraqi Freedom (OEF and OIF). METHODS: A retrospective review of children (<18 years old) in the Joint Theater Trauma Registry with isolated head injury (defined as an Abbreviated Injury Score Severity Code >3) and treated at a US combat support hospital in Iraq or Afghanistan (2004-2012). The primary outcome was in-hospital mortality. RESULTS: We identified 647 children with severe isolated head injuries: 337 from OEF, 268 from OIF, and 42 nontheater specific. Most were boys (76%; median age = 8 years). Penetrating injuries were most common (60.6%). Overall, 330 (51%) children underwent a craniotomy/craniectomy; 156 (24.1%) succumbed to their injuries. Admission Glasgow Coma Score was predictive of survival among the entire cohort and each of the individual conflicts. Male sex also significantly increased the odds of survival for the entire group and OEF, but not for OIF. Closed-head injury improved the predictive ability of our model but did not reach statistical significance as an independent factor. CONCLUSION: This is the largest study of combat-related isolated head injuries in children. Admission Glasgow Coma Score and male sex were found to be predictive of survival. Assets to comprehensively care for the pediatric patient should be established early in future conflicts. ABBREVIATIONS: CI, confidence interval GCS, Glasgow Coma Score ICP, intracranial pressure IED, improvised explosive device JTTR, Joint Theater Trauma Registry LN, local national MTF, military treatment facility OEF, Operation Enduring Freedom OIF, Operation Iraqi Freedom